KALIBRASI ARAH KIBLAT MASJID DI KECAMATAN MAKASSAR KOTA MAKASSAR - Amir, Rahma (UIN ALAUDDIN MAKASSAR, 2020)
This study examines the calibration of the qibla direction of mosques using a qualitative descriptive method through field research (Field Risearch), with the research object of matching the Qibla direction of several mosques in Makassar District. The approach in this study uses a syar'i, sociological approach. Researchers conducted a deductive and inductive analysis of the collected data. Then the tools used in this study were to use tools such as the Qibla Bow, Istiwa Sticks and Google Earth Applications. The measurement results from the use of tools in the form of Qibla Bow, Sticks of Istiwa and the Google Earth application produce different percentages of the two mosques in Makassar District. The percentages vary, including: 18o 28o 44o and 11o 18o 36o. Seeing the percentage results found from the calibration of the Qibla direction which is then combined with the sociological approach, there are two opinions, namely the management, the congregation and the general public who think that the direction of the Qibla is not enough to just point to the West but must face the direction of the Qibla. In fact, at the time of praying while the second part of the community around even the mosque administrators who still think that the direction of the Qibla is only a belief, it is not too important and is only a matter of direction or belief based on intention alone.